Network pharmacology, molecular docking, and experimental verification reveal the mechanism of San-Huang decoction in treating acute kidney injury - Liu, Jiahui; Li, Zhongtang; Lao, Yunlan; Jin, Xiaoming; Wang, Yuzhi; Jiang, Beibei; He, Riming; Yang, Shudong (Frontiers in Pharmacology, 2023)
Cisplatin, chemically named cis-diamminedichloroplatinum, is an effective anti-tumor drug. However, its usage is constrained by side effects such as nephron toxicity. Cisplatin-induced acute kidney injury (AKI) appears in approximately 20%-30% of cases. Despite the use of hydration and diuretics in clinical practice, it still occurs. Hence, finding an effective protective strategy against cisplatin-induced AKI is necessary. San-Huang decoction (SHD) comprises astragalus, rhubarb, and Sanqi, derived from Shen Nong's Materia Medica. SHD has good efficacy in treating chronic kidney disease (CKD). Consequently, we proposed that SHD has the potential for renal protection against cisplatin-induced AKI. Network pharmacology and experimental verification were used to explore the underlying mechanism of SHD. Through network pharmacology, we found that calycosin, rhein, and ginsenoside Rh2 may be SHD's primary active compounds in treating cisplatin-induced AKI, and AKT, TNF-α, IL-6, caspase-3, and MMP9 are the core target proteins. The relationship between the compound and target protein was further confirmed by molecular docking. The Gene Ontology (GO) and the Kyoto Encyclopedia of Genes and Genomes (KEGG) pathway analyses predicted that SHD has an anti-inflammatory role through the TNF and IL-17 signaling pathway. Moreover, Western blot and immunohistochemistry validated the potential molecular mechanisms of SHD, predicted from network pharmacology analysis. The mechanism of cisplatin-induced AKI involves apoptosis and inflammation. In apoptosis, Caspase-3, caspase-8, caspase-9, and Bax proteins were down-regulated, while bcl-2 was up-regulated by SHD. The differential expression of MMP protein is involved in the pathological process of AKI. MMP9 protects from glomerular tubule damage. MMP9 and PI3K/AKT anti-apoptosis pathway were up-regulated by SHD. In addition, we discovered that SHD alleviated AKI by inhibiting the NF-κB signaling pathway. This study provided evidence that SHD plays a critical role in anti-inflammation and anti-apoptosis via inhibiting the NF-κB signaling pathway and activating PI3K/AKT anti-apoptosis pathway,